Lung Cancer: New Directions in Senior Patients Assessment - Anca Iuliana Pîslaru; Sabinne-Marie Albișteanu; Adina Carmen Ilie; Ramona Ștefaniu; Aurelia Mârza; Ștefan Moscaliuc; Mălina Nicoară; Ana-Maria Turcu; Gabriela Grigoraș; Ioana Dana Alexa (Geriatrics, 2024)
Age is but one significant prognostic factor in lung cancer, influencing survival, treatment response, and outcomes. This narrative review synthesizes findings from searches of 11 leading databases of research studies, systematic reviews, book chapters, and clinical trial reports on lung cancer in senior patients, with a focus on geriatric assessment as well as biomarkers. Key prognostic factors for lung cancer in seniors include biological age, functional capability, physical and psychological comorbidities, frailty, nutrition, status, and biomarkers like DNA methylation age. We identified the most valuable assessments that balance efficacy with quality of life. Optimizing care and improving outcomes with senior lung cancer patients benefits from a tailored therapeutic approach incorporating a complex geriatric assessment. A multidisciplinary collaboration between geriatricians, oncologists, and pulmonologists is crucial.